2021
DOI: 10.3390/ijerph182111410
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health of Frontline Healthcare Workers in the United Arab Emirates during the COVID-19 Pandemic: A Snapshot of Summer 2020

Abstract: The study aim was to understand the availability of personal protective equipment (PPE) and the levels of anxiety, depression, and burnout of healthcare workers (HCWs) in the United Arab Emirates (UAE). This study was an online-based, cross-sectional survey during July and August 2020. Participants were eligible from the entire country, and 1290 agreed to participate. The majority of HCWs were females aged 30–39 years old, working as nurses, and 80% considered PPE to be available. Twelve percent of respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
18
0
2
Order By: Relevance
“… 59–62 Two different studies conducted in the UAE during the COVID-19 pandemic found that health care workers in the UAE suffer from anxiety, psychological distress and burnout. 62 , 63 However, our study mainly correlated the well-being of participants with social media practices, not with the type of work. 59–61 …”
Section: Discussionmentioning
confidence: 87%
“… 59–62 Two different studies conducted in the UAE during the COVID-19 pandemic found that health care workers in the UAE suffer from anxiety, psychological distress and burnout. 62 , 63 However, our study mainly correlated the well-being of participants with social media practices, not with the type of work. 59–61 …”
Section: Discussionmentioning
confidence: 87%
“…The UAE became the first country in the Middle East to announce a confirmed case of COVID-19 on 29 January 2020. 17 Since then, the government of the UAE has worked to identify gaps and priorities in terms of the healthcare workforce, facilities, and availability of both medical devices and personal protective equipment (PPE) as a response to the global crisis. As of July 21, 2022, a total of 978,966 cases of COVID-19 have been confirmed in the UAE, with 2329 corresponding deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Sun et al ( 16 ) discussed the following five main areas affecting patients with COVID-19: Attitudes toward the disease (fear, denial, and stigma); stress due to the nature of the disease, quarantine measures, and concerns regarding the health of family members; physical and emotional responses, such as lifestyle changes in diet, sleep, and behavior; supportive factors included psychological adjustments, medical care, and family and social support; and finally, gratitude through the cherishing of life, family, bravery, and tenacity. In the United Arab Emirates (UAE), studies have explored similarly the psychosocial impact of the COVID-19 on communities and special populations such as parents, children, university students, and health care professionals ( 17 ). However, so far exploring the effect and the impact of the COVID-19 diagnosis on the individual and the experience of the infected person has not been explored through an exploratory qualitative approach in the UAE.…”
Section: Introductionmentioning
confidence: 99%